Labour adjudication in India/ edited by Z.M.Sahid Siddiqi and M.Afzal Wani (New Delhi, 2001)
A wishful desire of every human being, for which one keeps striving throughout his life, is 'dignity. It is basically a matter of 'self possession" a fair social adjustment with dependable economic and ethical support. This is most essential for the growth, development and stability of an individual's personality. Accordingly 'dignity of all' is indispensable for social peace and equilibrium. There is no alternative to it. Historical scanning, however, reveals that the dignity of all' has been an exception rather than a rule in almost every human aggregate and culture. This has been particularly true with respect to 'dignity of labour'. But, there have been benefactors in every age who have ever kept striving for an egalitarian society; a society in which all could be equal and no one is either ranked in terms of his might or disdained because of his feebleness. The goal has, however, remained unattained in perpetuity. Notable has been the plight of the people in the working class. Being in a state of oppression, they have carried many derogatory labels on them, like, 'slaves', 'serfs' etc., reflecting their state of deprivation with no legal rights. Bereft of enforceable claims, they have remained a vendible commodity even up to the recent days of history. That all remained valid either under the approbating 'unwritten commands of the lords' or 'privileged inscriptions on the vellum' dictated by unchallenged masters of human property. Change has been reported since the specialized division of labour commenced, the industrialization expanded and the sense of contract strengthened. This was the dawn of the new era. Painful cries of suffering millions, with last hope to survive, came out from the ventils of the factory' shooting out a demand for dignity through law and not by mere courtesy. This led to the recognition of labour as a subject of justice and initiated the development of the corresponding legal regime. Though many issues have got the eye, the main task however, is yet unfinished.
Keywords: "Arbitration,Industrial-Indian"